Persistent cough after segmental resection, an issue that clinicians need to pay more attention to - Guan, He; Han, Zhijun; Wan, Qifei; Huang, Qiangwen; Wei, Li; Li, Jiwei (Frontiers in Oncology, 2025)
IntroductionPersistent cough after pulmonary resection can significantly impair a patient's quality of life. However, risk factors for persistent cough after pulmonary segmentectomy remain insufficiently described. This study aims to explore the risk factors for persistent cough following pulmonary segmentectomy and to establish a predictive model to guide perioperative management.MethodsThis retrospective study included 540 patients who underwent thoracoscopic pulmonary segmentectomy at Zhengzhou University People’s Hospital from February 2024 to January 2025. Data were divided into training and internal validation cohorts. Multivariate logistic regression analysis was performed using the training cohort to develop a predictive model. Data from 160 patients who underwent thoracoscopic pulmonary segmentectomy at Zhengzhou Seventh People’s Hospital from August 2024 to February 2025 were used for external validation. Both validation cohorts were used to evaluate the model’s reliability and its impact on patient outcomes.ResultsThere were no significant differences in the distribution of variables between the training and internal validation cohorts. Tobacco exposure (OR 0.19, 95% CI 0.07-0.49), tumor location (OR 2.36, 95% CI 1.27-4.36), type of surgery (OR 3.70, 95% CI 2.18-6.29), vagus nerve injury (OR 2.15, 95% CI 1.23-3.76), and drainage duration (OR 1.48, 95% CI 1.29-1.70) were identified as independent risk factors for persistent cough after surgery. The predictive model derived from multivariate analysis demonstrated high diagnostic value (AUC = 0.80), and the Hosmer-Lemeshow test indicated good model fit (P = 0.818). Both internal and external validation analyses confirmed the model’s reliability and substantial net benefit for patients.DiscussionPersistent cough is a common postoperative complication following pulmonary segmentectomy and should receive greater clinical attention. Tobacco exposure, tumor location, type of surgery, vagus nerve injury, and drainage duration were identified as independent risk factors for persistent cough after surgery. Visualizing these risk factors aids in assessing the likelihood of persistent cough after pulmonary segmentectomy and provides valuable support for clinical decision-making.